Haematobia Le Peletier & Serville 1828 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Haematobia Le Peletier & Serville, 1828 Haematobia Le Peletier & Serville in Latreille et al ., 1828: 499 (as a subgenus of Stomoxys Geoffroy, 1762). Type-species: Conops irritans Linnaeus, 1758, by designation of Westwood (1840: 140) and validated by I.C.Z.N., Opinion 1008 (1974: 157–158). Haematobia irritans (Linnaeus, 1758) Conops irritans Linnaeus, 1758: 604. Type-locality: not stated (presumably Sweden). Lectotype ♂, LSUK (designated by Pont, 1981a: 169). Siberian records: Middle and South Urals (Zagrebin, 1989: 20; 1992: 60); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 231); Chelyabinskaya Oblast’, Troizkiy Rayon (Kutuzova, 1993: 74, 75); Tyumenskaya Oblast’, common in forest steppe, rarer in subtaiga and southern taiga (Veselkin, 1966: 783); Kurganskaya Oblast’ (Veselkin, 1989: 11); Baykal-Amur railway (Veselkin, 1981: 371); West and East Siberia (Pont, 1986a: 109). General distribution: Holarctic and Neotropical Regions, also Hawaii. Haematobia thirouxi titillans (Bezzi, 1907) Lyperosia titillans Bezzi, 1907: 454. Replacement name for irritans of Rondani (1862) and Pandellé (1898) in part, not Linnaeus, 1758 (misidentifications). Type-localities: Italy, Parma district, Calabria and the Alps; and France, Landes and Paris. Syntypes ♂ ♀, MZUF, MNHN, 11♂ 2♀, MCSNM (seen), 1♂, BMNH (Pont, 1990: 169), and 1♂, IPP (seen). Siberian records: Chelyabinskaya Oblast’, Troizkiy Rayon (Kutuzova, 1993: 74, 75); Tyumenskaya Oblast’, forest steppe, subtaiga and southern taiga (Veselkin, 1966: 787); Kurganskaya Oblast’ (Veselkin, 1989: 11); Tyumen’ and Omsk (Veselkin, 1972: 270–271); Baykal-Amur railway (Veselkin, 1981: 371); South Tyva (Lake Shara-Nur and River Naryn-gol) (Pridantseva, 1959: 145–155); South Tyva, River Naryn-gol (Pridantseva, 1967: 828); Respublika Tyva (Tamarina & Khromova, 1980: 81); South Siberia (Hörning, 1959: 340); West and East Siberia (Pont, 1986a: 109). General distribution: Palaearctic Region, from Europe east to China, also India ...